PINOID is required for lateral organ morphogenesis and ovule development in cucumber. (13th August 2019) - Liu, Xiaofeng; Hao, Ning; Li, Huiyuan; Ge, Danfeng; Du, Yalin; Liu, Renyi; Wen, Changlong; Li, Yuhong; Zhang, Xiaolan; Wu, Tao
Abstract : CsPID regulates the morphogenesis of leaf, tendril, and floral organs, as well as ovule genesis, by modulating the expression of genes related to auxin transport and ovule development, and by interacting with the polarity regulator CsREV. Abstract: Lateral organ development is essential for cucumber production. The protein kinase PINOID (PID) participates in distinct aspects of plant development by mediating polar auxin transport in different species. Here, we obtained a round leaf ( rl ) mutant that displayed extensive phenotypes including round leaf shape, inhibited tendril outgrowth, abnormal floral organs, and disrupted ovule genesis. MutMap + analysis revealed that rl encodes a cucumber ortholog of PID ( CsPID ). A non-synonymous single nucleotide polymorphism in the second exon of CsPID resulted in an amino acid substitution from arginine to lysine in the rl mutant. Allelic testing using the mutant allele C356 with similar phenotypes verified that CsPID was the causal gene . CsPID was preferentially expressed in young leaf and flower buds and down-regulated in the rl mutant. Subcellular localization showed that the mutant form, Cspid, showed a dotted pattern of localization, in contrast to the continuous pattern of CsPID in the periphery of the cell and nucleus. Complementation analysis in Arabidopsis showed that CsPID, but not Cspid, can partially rescue the pid-14 mutant phenotype. Moreover, indole-3-acetic acid content was greatly reduced in the rl mutant. Transcriptome profiling revealed that transcription factors, ovule morphogenesis, and auxin transport-related genes were significantly down-regulated in the rl mutant. Biochemical analysis showed that CsPID physically interacted with a key polarity protein, CsREV (REVOLUTA). We developed a model in which CsPID regulates lateral organ morphogenesis and ovule development by stimulating genes related to auxin transport and ovule development.